2021
DOI: 10.1002/advs.202004036
|View full text |Cite
|
Sign up to set email alerts
|

Natural Clay‐Based Materials for Energy Storage and Conversion Applications

Abstract: Among various energy storage and conversion materials, functionalized natural clays display significant potentials as electrodes, electrolytes, separators, and nanofillers in energy storage and conversion devices. Natural clays have porous structures, tunable specific surface areas, remarkable thermal and mechanical stabilities, abundant reserves, and cost‐effectiveness. In addition, natural clays deliver the advantages of high ionic conductivity and hydrophilicity, which are beneficial properties for solid‐st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 157 publications
0
53
0
1
Order By: Relevance
“…[24,25] Moreover, MMT has other advantages as a naturally existing 2D layered material, such as a tunable interlayer space, a high adsorption capacity, a high cation exchange capacity, widespread abundance, low cost, and environmental friendliness. [29] Therefore, it shows great potential for applications in LiÀ S batteries. However, it is important to note that high conductivity of MMT based host material is critical for high-performance LiÀ S batteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24,25] Moreover, MMT has other advantages as a naturally existing 2D layered material, such as a tunable interlayer space, a high adsorption capacity, a high cation exchange capacity, widespread abundance, low cost, and environmental friendliness. [29] Therefore, it shows great potential for applications in LiÀ S batteries. However, it is important to note that high conductivity of MMT based host material is critical for high-performance LiÀ S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Xiong and coworkers have demonstrated that MMT has a strong chemisorption capacity for LiPSs and the atomic interlamellar ion pathways in MMT can guarantee a low energy barrier for lithium‐ion diffusion, which enables the sulfur cathode to achieve a sulfur‐loading‐independent performance [24,25] . Moreover, MMT has other advantages as a naturally existing 2D layered material, such as a tunable interlayer space, a high adsorption capacity, a high cation exchange capacity, widespread abundance, low cost, and environmental friendliness [29] . Therefore, it shows great potential for applications in Li−S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1b, these solid electrolytes are composed of bentonite clay, PEO and ionic liquid (for detailed preparation method, see Figure S1 in the Supporting Information). Furthermore, the main component of bentonite clay is layer‐structured montmorillonite consisting of a silicon‐oxygen tetrahedra and aluminum‐oxygen octahedra crystal structure (2 : 1 ratio; Figure S2) [29,30] . A large number of Si−O bonds make it negatively surface‐charged.…”
Section: Resultsmentioning
confidence: 99%
“…体材料 [1] ,且以矿物材料为主要或重要组分的复合材料 [2] 。其中的矿物组分可以包括工业矿物与岩石,不仅可 以是以长石、石英、铝土矿等为代表的工业矿物原料,也可以是包括天然矿物材料和人工矿物材料的工业矿物 材料 [3] ,如石墨、云母、沸石等,还有以高岭土、膨润土为主的工业岩石原料和工业固体废物等。 随着科学技术发展和社会进步,地球科学的矿物学与材料科学的复合材料学得以交叉融合创新发展。矿物 复合材料作为一类新型复合、融合与杂化材料逐渐被研究者们提出并接受 [1~9] 。美国亚利桑那大学 Paul Calvert 等人 [4] 认为,纳米矿物材料具有很多有趣的特性,但往往需要借助微妙的表面处理或通过渗透一个相来发挥其 作用, 如层状硅酸盐矿物填充聚合物复合材料的力学性能随矿物含量的提升往往比球形纳米颗粒填充聚合物效 果要好。随后,美国康奈尔大学 Giannelis 研究组 [5] 、麻省理工学院 Thomas 研究组 [6] 相继报道了蒙脱石矿物插 层纳米结构及其力学性能和阻隔性能等有关研究。例如,Giannelis 研究组 [7] 设计了一种以层状硅酸盐为无机增 强体的材料,利用高分子复合的制备方法将层状硅酸盐插入单体和聚合物的层与层之间,并通过离子交换反应 实现了烷基铵阳离子衍生硅酸盐与各种聚合物的相容性。本研究组 [8] 利用蒙脱石制备了层状硅酸盐纳米复合薄 膜,认为在聚酰亚胺基体中加入适量蒙脱土,可同时提高室温和超低温度下的强度、模量和延展性。随着科技 的发展,矿物复合材料逐渐步入材料科学研究领域,由此得到的聚合物基层状硅酸盐纳米复合材料表现出了与 传统黏土复合材料不同的硬度、强度和阻隔性能。后来,随着人们对天然复合材料认知的深入和提升,使得矿 物复合材料也融入了天然材料的设计理念,为矿物复合材料的设计开创了新的理念,为矿物复合材料学科分支 的形成、发展及应用奠定了良好基础。例如,鲍鱼壳 [9] 是一种碳酸钙和有机材料组成的天然复合材料,其抗断 裂性比纯矿物的单晶高 5000 倍。Stupp 研究组 [10] 使用 pH 诱导肽两亲物自组装来构造纳米结构的纤维状支架并 诱导羟基磷灰石矿化,使羟基磷灰石沿晶体学 c 轴与有机纤维平行生长,得到的类骨骼状层次结构,为矿物复 合材料的医学应用 [11] 奠定了基础。 现如今,随着国际材料科学的发展和我国对新能源技术和生态环境保护的大力支持,能量存储与能源催化 材料已逐渐成为功能材料领域的研究热点。例如,由天然矿物石墨衍生出的石墨烯复合材料 [12] 和黏土矿物插层 复合材料 [13] 已经在储能、催化、光电、生物医药等领域大放异彩。由天然辉钼矿衍生出的二维 MoS 2 [14] 复合材 料具有典型的半导体特性;Ajayan 研究组 [15] 从天然赤铁矿(α-Fe 2 O 3 )中分离得到一种新的二维材料赤铁矿烯, 将其负载于二氧化钛纳米管阵列时,表现出优异的光化学能量转换效应,以及继承天然矿物的过渡金属氧化物 [16] 、硫化物复合材料 [17] 的多价离子存储、电催化应用等。因此,下一代矿物复合材料的形态、功能和应用很 可能会随着人类对材料物理机制的挖掘而不断地丰富和增长(图 1) 。 [1] ,矿物复合材料往往可分为层状插层矿物复合材 料 [18] (蒙脱石、高岭石、蛭石、累托石、云母等复合材料) 、链状硅酸盐矿物复合材料 [19] (凹凸棒石、海泡石、 硅灰石等复合材料) 、多孔矿物复合材料 [20] (硅藻土、沸石和膨胀珍珠岩等复合材料) 、石墨矿物复合材料(改 性石墨和石墨烯复合材料) 、矿物纤维复合材料 [21] (玄武岩纤维、岩棉纤维、硅酸铝纤维、水镁石纤维、硅灰 A c c e p t e d https://engine.scichina.com/doi/10.1360/TB-2021-0667 石纤维等复合材料) 、尾矿复合材料 [22] (粉煤灰、煤矸石、微硅粉、矿物聚合物和改性赤泥等复合材料)和其 他矿物复合材料(碳酸钙、水镁石、重晶石等复合材料 [23] )等。按照其应用领域,可以分为矿物复合能源存储 材料、矿物复合生态环境材料、矿物复合生物医药大健康材料、矿物复合光电信息材料等。 根据矿物组分,可将矿物在矿物复合材料中的作用分为三种: (1)矿物功能单元:本身具有直接应用功能属性的矿物,如黄铁矿复合材料用于钠离子存储 [24] ;赤铁矿 复合材料用于超级电容器 [25] ;辉钼矿复合材料用于 HER [26] 等。 (2)矿物结构单元:本身无直接功能属性,主要起分散性、负载性等结构性作用。如埃洛石复合材料用 于光催化 HER [27] ,尾矿复合材料用于资源化综合利用 …”
Section: 矿物复合材料是指组成复合材料的多种组分中, 含有一种或多种矿物组分从而使材料具有新性能的多相固unclassified